Land Use/Cover Change Detection in Arid and Semi-Arid Areas of Northeastern Jordan Using Landsat Images - Al-Bilbisi, Hussam (Jordan Journal of Social Sciences, 2017)
Digital change detection is the method that facilitates in determining the changes associated with land use and land cover properties using multi temporal remote sensing data. This paper is an attempt to assess the changes in land use/land cover in arid and semi-arid areas of northeastern part of Jordan. For this purpose a subset of each of the Landsat-TM and Landsat-8 digital images acquired in May, 2000, and May, 2014, respectively, were used. The two multi-temporal images were geometrically and radiometrically calibrated to each other, and then were classified using Maximum Likelihood classification algorithm. Change detection results showed that the decline of herbaceous areas is clearly the result of accelerated expansion of the bare land area class in the studied area. This paper highlights the importance of digital change detection in northeastern part of Jordan.